Model Matematika Jumlah Pemakai Narkoba dengan Program Rehabilitasi - Eli Yuliza; Media Rosha; Riry Sriningsih (UNIVERSITAS NEGERI PADANG, 2014)
Abstract–In the number of drug users in Indonesia each year has increased very significantly, so this problem should be addressed immediately.Currently, the government has organized rehabilitation program that is expected to reduce the number of drug users in the future. To predict the number of drug users, can be done by creating a mathematical model of the number of drug users. Mathematical model number of drug users in rehabilitation programs dividing the population into four groups of individuals: the group of susceptible individuals for drug use, drug user groups of individuals, groups of individuals are rehabilitated, and a group of individuals who have stopped using drugs. Mathematical model that formed were analyzed by looking at the stability, the analysis of mathematical models obtained two types of fixed points. In the number of drug users is affected by four parameters: the level of interaction between individuals prone to drug use by individual drug users, the level of individual drug users to be individuals who stop using drugs, and individual level drug offenders to be rehabilitated individuals. Keywords–Drugs, mathematical model, fixed point.